The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1080/02671522.2012.742132
|View full text |Cite
|
Sign up to set email alerts
|

Socratic questioning in the Paideia Method to encourage dialogical discussions

Abstract: This study focused on the impact of using Socratic questioning, based on the Paideia Method, on the nature of middle-schools students' patterns of interaction and on the cognitive complexity of their discussions. The hypothesis is that an experimental group will increase in both interaction focus and complexity at T3, which is the face-to-face seminar when compared to T1 (baselines) and that this increase will be above normative increases compared to a control group. A quasi-experimental method was employed be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 25 publications
(31 reference statements)
0
9
0
Order By: Relevance
“…To promote productive talk about text and give students greater control over the flow of information, teachers use the discourse tools of 'asking authentic questions that Quality talk -an examination of a professional development programme 971 invite a range of responses, employing uptake to build on students' contributions, and asking questions to elicit high-level thinking (generalization, analysis, and speculation)' (Quality Talk, 2012). Furthermore, the teacher is expected to follow pedagogical principles which the Quality Talk developers, drawing on the literature and research on the role of the teacher, deem important to good discussion: using rich, interesting texts, collaboratively establishing ground rules for discussions (Walshaw & Anthony, 2008), asking a thought-provoking statement or 'big question' (Adler, 1983) to initiate a discussion in which the students' opinions are likely to differ (Davies & Sinclair, 2014) and encouraging exploratory talk .…”
Section: The Quality Talk Approach: a Scaffold For Teachers To Implemmentioning
confidence: 99%
See 1 more Smart Citation
“…To promote productive talk about text and give students greater control over the flow of information, teachers use the discourse tools of 'asking authentic questions that Quality talk -an examination of a professional development programme 971 invite a range of responses, employing uptake to build on students' contributions, and asking questions to elicit high-level thinking (generalization, analysis, and speculation)' (Quality Talk, 2012). Furthermore, the teacher is expected to follow pedagogical principles which the Quality Talk developers, drawing on the literature and research on the role of the teacher, deem important to good discussion: using rich, interesting texts, collaboratively establishing ground rules for discussions (Walshaw & Anthony, 2008), asking a thought-provoking statement or 'big question' (Adler, 1983) to initiate a discussion in which the students' opinions are likely to differ (Davies & Sinclair, 2014) and encouraging exploratory talk .…”
Section: The Quality Talk Approach: a Scaffold For Teachers To Implemmentioning
confidence: 99%
“…Smith and Higgins’ () large‐scale research project concluded that to ‘open up’ classroom interactions, emphasis should be less on the questions teachers ask and more on the manner with which teachers react to pupils’ responses to questions. Yet there is also clear evidence that the initial provocation or ‘big’ question to stimulate, engage and motivate students to participate is important for the dialogical discussion to be effective (Davies & Sinclair, ).…”
Section: Dialogic Teaching: Teaching Practice To Foster Positive Studmentioning
confidence: 99%
“…Additionally, the teacher's role is to begin with an openended, thought-provoking question and then allow students to build on each other's comments via textual evidence. The Paideia Seminar requires students to articulate and examine their own thinking, not replay the thoughts of the teacher, as they defend and clarify their own ideas and those of others (Roberts & Billings, 1999) This strategy provides opportunity for student voice, promotes greater autonomy, and stimulates active comprehension in students (Billings & Fiztgerald, 2002;Davies & Sinclair, 2014). The conclusion of the Paideia Seminar cycle requires that students write a reflection to synthesize their new understanding.…”
Section: Empirical Research On Paideia Seminarsmentioning
confidence: 99%
“…However, there is little current research on translanguaged Paideia Seminars, which focus on emergent bilingual students' contributions during critical literacy discussions. In fact, in a study conducted by Davies & Sinclair (2014), the researchers observed that lower socio-economic classrooms, especially those with many EBLs, required more teacher interaction and less time for co-construction of meaning among students. It is possible that EBLs may not communicate during Paideia Seminars because of a dominating teacher or student voices in the room, having limited background knowledge of the topic, or being unable to adequately express their opinions in a language they are still learning (Rubinstein-Avila, 2006;Valdés, 2001).…”
Section: Empirical Research On Paideia Seminarsmentioning
confidence: 99%
“…Socratic teaching and learning stresses student-centeredness and strongly opposes lecturing. 20 Socratic questioning has been used in various types of education, 21 24 and many studies have addressed the effectiveness of this method in teaching ethics. 25,26 Socratic questioning, which stresses reflection and reasoning, has been referred to as the most effective method of developing critical thinking.…”
Section: Introductionmentioning
confidence: 99%